1522. Initial Clinical Response of Children with Extended-Spectrum Cephalosporin-Resistant Urinary Tract Infections (ESC-R UTI's) Started on Discordant Antibiotics. (26th November 2018) - Wang, Marie; Lee, Vivian; Greenhow, Tara; Beck, Jimmy; Bendel-Stenzel, Michael; Hames, Nicole; McDaniel, Corrie; King, Erin; Sherry, Whitney; Parmar, Deepika; Patrizi, Sara; Srinivas, Nivedita; et al.
Abstract: Background: ESC-R UTI's in children are often resistant to common empiric regimens. Our objective was to describe the initial clinical response of children with ESC-R UTI's while on discordant antibiotics. Methods: We conducted a multicenter retrospective chart review of children < 18 years with ESC-R UTI's presenting to an acute care setting of 5 children's hospitals and a large managed care organization from 2012 to 2017. ESC-R UTI was defined as having a urinalysis with positive leukocyte esterase or >5 white cells per high-power field and urine culture with ≥50, 000 colony-forming units per milliliter of E. coli or Klebsiella spp. nonsusceptible to ceftriaxone. Children were included if they received initial discordant antibiotics (an agent to which their isolate was nonsusceptible) and had phone or in-person follow-up when urine culture susceptibilities resulted. Children with urologic surgery, immunosuppression and nonrenal chronic conditions were excluded. Outcomes were: (1) Escalation of care, defined as an emergency room visit, hospital admission or intensive care unit (ICU) transfer while on discordant therapy and (2) clinical response at the time of follow-up, classified as improved (complete or partial resolution of presenting symptoms) or not improved (persistence of symptoms) and assessed by a second reviewer in 20% of charts to determine inter-rater reliability. Results: Of 253 children with ESC-R UTI's, 76% were female, median age was 2 years (interquartile range [IQR] 0.5–6.5) and 88% were started on cephalosporins. Median time to follow-up was 3 days (IQR 2–3). Nine children (4%) had escalation of care without ICU transfer. Follow-up records with clinical response information were available for 187 children (74%); 154 (83%) were improved and 33 (17%) were not improved ( κ = 0.80). Figure 1 shows improvement by symptom. In children with repeat urine testing while on discordant therapy, pyuria improved in 12/15 and urine cultures sterilized in 10/13. Conclusion: Most children with ESC-R UTI's experienced initial clinical improvement while on discordant antibiotics. Future studies should prospectively evaluate the in vitro and clinical effect of discordant therapy in children to assess the need for modified urine-specific breakpoints. Disclosures: All authors: No reported disclosures.